1992
DOI: 10.1515/jpme.1992.20.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Determination of t-PA activity and t-PA antigen in human milk

Abstract: Although a considerable number of publications on tissue plasminogen activator (t-PA) in human milk have appeared, most investigators have determined t-PA activity using an assay on fibrin plates [1, 2, 3, 4]. We measured t-PA activity by a bioimmunoassay and t-PA antigen by ELISA using a monoclonal antibody (SP-322) [6], and estimated t-PA index ((t-PA activity, ng/ml)/(t-PA antigen, ng/ml) x 100) in human colostrum and milk to evaluate the fluctuations of post-delivery t-PA. The concentrations of t-PA activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Forty four randomised trials (7278 women) reported the effects of dietary and lifestyle interventions in pregnancy. The interventions in the trials were broadly classified into three groups: those mainly based on diet (13 randomised trials)24 25 26 27 28 29 30 31 32 33 34 35 36 or physical activity (18 randomised trials)37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 and a mixed approach with diet and physical activity components that might or might not be underpinned by behavioural counselling (13 randomised trials) 756 57 58 59 60 61 62 63 64 65 66 67…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty four randomised trials (7278 women) reported the effects of dietary and lifestyle interventions in pregnancy. The interventions in the trials were broadly classified into three groups: those mainly based on diet (13 randomised trials)24 25 26 27 28 29 30 31 32 33 34 35 36 or physical activity (18 randomised trials)37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 and a mixed approach with diet and physical activity components that might or might not be underpinned by behavioural counselling (13 randomised trials) 756 57 58 59 60 61 62 63 64 65 66 67…”
Section: Resultsmentioning
confidence: 99%
“…The included trials studied the effect of interventions on women with any BMI,7 25 26 27 28 29 30 32 37 38 39 40 42 43 44 45 46 47 48 49 50 52 54 55 56 57 58 59 60 61 62 63 64 65 66 mostly obese and overweight women,31 33 53 or only obese women24 29 34 35 36 51 59 67 (clinical characteristics of all identified studies are in appendix 3 on bmj.com). Five randomised trials included pregnant women with a diagnosis of gestational diabetes mellitus28 31 34 57 58 and one included women with pre-existing diabetes 32.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the original 44 papers included within the Thangaratinam et al review [ 3 ], one study only consisted of a conference abstract [ 26 ]. Full-text versions of all of the other articles were obtained.…”
Section: Resultsmentioning
confidence: 99%